(untitled) (Research, Society and Development, 2022)
Objective: To analyze aspects related to the experience of mourning in family members of those who died by COVID-19 in the hospital environment. Methodology: Study with a qualitative approach, developed in a referral hospital in Ceará, between March and June 2020. The data were analyzed by the IRAMUTEQ software, where the descending hierarchical classification was obtained to assess the dendrogram data according to the generated classes and of the word cloud. Results: Eleven family members of patients who died from COVID-19 in a hospital participated in the study. The analyzed content was categorized into four classes: Class 1 – recognition of the body after death, with 10 ST (29.41%); Class 2 – the death notice, with 12 ST (35.29%); Class 3 - social isolation in the face of the ban on visits, with 06 ST (17.65%) and Class 4 - feelings in the general context of family loss by COVID-19. Conclusion: The news of the death was passed on to the family members with coldness and detachment on the part of the professionals. There was a negative impact due to the change in farewell rituals on the verge of dying and the recognition of the body by the family member.